Design and implementation of foreign language teaching system based on cloud platform - Wu, Liang (SPIE, 2024)
With the maturity of big data analysis technology, the emergence of cloud learning platforms oriented to distributed computing and other computing has promoted the reform and innovation of modern education technology. The modern teaching environment has changed. Course teaching gradually changed from traditional closed teaching to open integration based on cloud platform. The development method of cloud platform teaching system mainly includes the establishment and maintenance of the backend database, the intermediate business is the processing of the album and the display and interaction of the front-end interface data. The system consists of three roles: students, teachers, and administrators, and realises a number of functions including student registration, information query, course learning, online examination, and interactive message. Road through the use of the conclusion is to show that the system has a good user interface, can effectively reduce the teacher's workload, effectively improve the efficiency of student learning, but also to help students learn independently, to strengthen the teacher-student communication, to cultivate better learning nitrogen perimeter. The system development tools for MyEclipse integrated development environment, JAVA language as the main programming, SQL Sever as the background database, JSP written user interface, through the background analysis and then synthesise the data displayed to the front-end, can be deployed in the AliCloud platform, the purchase of servers, open tomcat and the server port, you can move through the IP ask. Most of the interactive learning in traditional teaching is concentrated in the offline classroom because of the geographical location limitation, and the offline communication can only be carried out by the same classmates, but in the online classroom of the cloud platform, it is not limited to the geographical location of the class, and it is possible to study anytime and anywhere on the network, and it is also possible to leave a message and comment under the course, and it is possible to learn and discuss with each other across the classes and even across the schools, and it is possible to supervise and learn and progress with everyone together. Learning and progressing together. For most of the system, this system can provide students with cloud learning process, but also provide students and teachers to register, login function, which includes a variety of tools module, similar to the background module of the course management, the foreground module of the course online learning, learning notes, etc., the cloud education system can provide timely feedback on students' learning, so that the students' learning efficiency and gain greatly improved, that is, for the time and some of the Unsolvable difficult problems are greatly improved and solved. Cloud platform teaching system is an online system that can provide great help for everyone's learning and life online learning.